2015
DOI: 10.1007/s11695-015-2031-x
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal-Jejunal Bypass Preferentially Elevates Serum Taurine-Conjugated Bile Acids and Alters Gut Microbiota in a Diabetic Rat Model

Abstract: DJB preferentially increases serum taurine-conjugated BAs, probably because of more BA reabsorption in the terminal ileum. The gut microbiota is altered with more Firmicutes and Proteobacteria and less Bacteroidetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 46 publications
4
31
0
2
Order By: Relevance
“…An upregulation of the abundance of Bacteroidetes was observed on animal experiences after RYGB (19,27) and SG (31). However, contrary results were provided on rats after DJB (28). Two studies reported the increase of the phylum Fusobacteria in 2016 (19,22).…”
Section: Microbiota Altered On Strong Evidencementioning
confidence: 96%
See 1 more Smart Citation
“…An upregulation of the abundance of Bacteroidetes was observed on animal experiences after RYGB (19,27) and SG (31). However, contrary results were provided on rats after DJB (28). Two studies reported the increase of the phylum Fusobacteria in 2016 (19,22).…”
Section: Microbiota Altered On Strong Evidencementioning
confidence: 96%
“…An increased population of Proteobacteria was observed in diet-induced mice with obesity after RYGB (27). Experimental results on rats showed an increase of Proteobacteria after DJB (28) and RYGB (19,25). In addition, Li et al found substantial shifts of the main gut phyla toward higher concentrations of Proteobacteria, specifically Enterobacter hormaechei (E. hormaechei), from a non-obese rat model characterizing the effect of RYGB (29).…”
Section: Microbiota Altered On Strong Evidencementioning
confidence: 99%
“…Thus, in order to have a better understanding of the relationship between bariatric surgery, gut microbiota, and SCFA, we studied changes in the gut microbiota and SCFA following DJB-sa surgery in Goto-Kakisaki (GK) rats and determined whether these changes were associated with improved glucose metabolism. By applying this model of diabetes, the potential mechanisms by which DJB-sa is beneficial to T2DM patients can be explained from a new perspective (Arora and BĂ€ckhed, 2016;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a long-term stability of the changes observed has been recently reported by Tremaroli et al [36]. In addition, in animal models, Zhang et al have recently observed after duodenal-jejunal bypass in a diabetic rat model an increase of Firmicutes and Proteobacteria but a decrease of Bacteroidetes [37].…”
Section: Surgerymentioning
confidence: 54%